Pathology of Urinary Bladder in Pearsonema spp. Infected Wildlife from Central Italy - Claudia Eleni; Alessia Mariacher; Goffredo Grifoni; Elena Cardini; Sara Tonon; Andrea Lombardo; Antonino Barone; Gianluca Fichi (Pathogens, 2021)
The genus Pearsonema, in the nematode family Capillariidae, includes several species that parasitize the urinary bladders of wild and domestic carnivores. The infection has been reported worldwide from several wildlife species, including canids, mustelids, and felids, but the pathological aspects have seldom been investigated. In order to assess the presence and severity of the lesions in Pearsonema-infected wildlife, we performed a parasitological and pathological examination of urinary bladders from 72 animals, belonging to the families Canidae (red fox Vulpes vulpes, n = 28, and wolf Canis lupus, n = 29) and Mustelidae (beech marten Martes foina, n = 3; pine marten Martes martes, n = 2; and European badger Meles meles, n = 10). A greater prevalence of infection for canids (64.91%; 95% confidence interval (95% CI), 52.52–77.30%) than for mustelids (13.33%) (p < 0.001) was recorded. The prevalence of infection in red foxes was 75.0% (95% CI, 58.96–91.04%), in accordance with other reports from European countries, supporting the role of this species as a reservoir for infection. Eosinophilic cystitis was observed in 34 out of the 72 examined animals (47.22%). The influence of Pearsonema sp. infection on the occurrence of eosinophilic cystitis was statistically significant in wolves (p < 0.01), which were also affected by more severe histological lesions compared to foxes.